Role of soil fauna to litter decomposition in pine stands under Atlantic Forest biome - Pech, Tatiani (2021)
Litter production and its decomposition play an important role in the terrestrial carbon cycle and soil quality, being a crucial process involved in ecosystem productivity and functioning. Understanding this process under pine commercial stands or pine invasions is crucial to design forest management or ecosystems restoration. We conducted a study in a commercial pine plantation (Pinus taeda L.) under Atlantic Forest biome to investigate (1) the contribution of soil fauna to pine litter mass loss; (2) the litter fauna feeding activity within seasons. Litter bags with pine needles (5 g dry weight) were prepared as exclusion treatments for different sized soil fauna by varying mesh size (2 mm and 0.06 mm). Litter bags were removed after 60, 120, 180, 240, 300, and 365 days to estimate the decomposition rates. Bait lamina sticks were exposed seasonally and horizontally in soil surface to determine the fauna feeding activity on litter. We found: (1) no differences in litter mass loss and decomposition rate when soil macrofauna and most of the mesofauna were excluded; (2) feeding activity of litter organisms was higher in the summer, probably stimulated by a combination of high temperature and rainfall. In commercial pine stands, we can conclude that the nutrient cycling is slower than in natural areas, related to litter traits, as described in the scientific literature. Our results indicated that soil macro and mesofauna play a low role in the pine litter decomposition, where the organic material decomposition is more related to microorganism’s activity.